Analysis of the Implementation of Poac Principles in the Management of Parking Tax at Sultan Hasanuddin International Airport and its Contribution to Regional Original Revenue of Maros Regency - Muhammad Ikram Idrus; Abdul Hafid Burhami; Nada Nabila Syarma (Universitas Muhammadiyah Makassar, 2023)
This study aims to implement POAC by the Regional Government of Maros Regency in terms of managing parking taxes originating from Sultan Hasanuddin International Airport in Maros and an overview of the amount of parking tax contributions originating from Sultan Hasanuddin International Airport in supporting the PAD of the Maros Regency Government. The source of the data in this study is the data needed is sourced from the internal government of Maros Regency, in this case at the Office of the Regional Revenue and Finance Management Agency (BPKPD) of Maros Regency. With a research period of 6 (six) months from January to June 2021. The analytical method used in this study is POAC, Contribution of taxes to PAD and describes parking tax management and its contribution to PAD of the Maros Regency Government based on observations of the use of POAC principles. The results of this study were that the Maros Regency Government in managing parking tax revenues originating from the Sultan Hasanuddin International Airport in Maros had worked based on the POAC principle (Planning, Organizing, Actuating and Controlling). The results of the observations show that: Planning, the implementation is not interpreted optimally, Organizing, the implementation is interpreted quite well but not optimal, Actuating, the implementation is interpreted in a good category. Controlling, the implementation is interpreted in good category. And the parking tax contribution of Sultan Hasanuddin International Airport in Maros in supporting Maros Regency's Original Revenue is an average of 4.9% in the 2015 - 2019 period.